INTERVENSI KOMUNITAS SABANGMERAUKE DENGAN COMPETENCY BASED INTERVIEW - Penny Handayani; Reneta Kristiani; Naomi Hanalisa; F. Resa Kawatu; Linda Benita; Karina Lois; Katherine Katherine (Jurnal Bakti Masyarakat Indonesia, 2020)
This research aims to explore the issues of volunteer engagement faced by the SabangMerauke Community that affect the level of voluntary self-belonging to the community. This research is a type of descriptive research with a descriptive research method approach. Determination of research subjects using purposive sampling techniques. Based on this technique, the subjects of this study were all administrators and volunteers of the SabangMerauke Community and the participants involved such as the SabangMerauke Brother, Sister and Family. Data collection techniques used were interviews and questionnaires online. Interventions given to the SabangMerauke community are interventions in the process of recruiting volunteers using competency-based interview techniques. The conclusion from the series of interventions provided is that the provision of training for trainers to the SabangMerauke Community is appropriate and targets what they need. This is based on the group's assessment of the success indicator checklist that was designed before the training for trainers took place. Apart from the indicators of success, there is concrete evidence that shows the success of this intervention, namely the response and activeness of the two respondents present. Besides listening, they also asked a number of questions and actively confirmed their knowledge to the group by discussion. The community also asked the group to be able to follow up the community recruitment process the following year. Although in terms of interventions classified as successful, but there are some obstacles experienced by groups such as interventions that can only be done once because it follows the schedule of the community administrator.ABSTRAK:Penelitian ini bertujuan untuk menggali permasalahan volunteer engagement yang dihadapi Komunitas SabangMerauke yang mempengaruhi tingkat self-belonging relawan terhadap komunitas. Penelitian ini merupakan jenis penelitian deskriptif dengan pendekatan metode penelitian deskriptif. Penentuan subjek penelitian menggunakan teknik purposive sampling. Berdasarkan teknik tersebut, subjek penelitian ini adalah seluruh pengurus dan relawan Komunitas SabangMerauke serta para peserta yang terlibat seperti Kakak, Adik dan Famili SabangMerauke. Teknik pengumpulan data yang digunakan adalah wawancara dan penyebaran kuesioner online. Intervensi yang diberikan untuk komunitas SabangMerauke adalah intervensi dalam proses perekrutan relawan dengan teknik competency-based interview. Kesimpulan dari rangkaian intervensi yang diberikan adalah pemberian training for trainers kepada Komunitas SabangMerauke sudah tepat dan menyasar pada apa yang mereka butuhkan. Hal ini didasari atas penilaian kelompok terhadap checklist indikator keberhasilan yang telah dirancang sebelum training for trainers berlangsung. Selain dari indikator keberhasilan, terdapat bukti nyata yang menunjukkan keberhasilan intervensi ini yaitu respon dan keaktifan dari kedua responden yang hadir. Selain mendengarkan, mereka juga melontarkan beberapa pertanyaan serta secara aktif mengkonfirmasi pengetahuan mereka kepada kelompok dengan berdiskusi. Pihak komunitas juga meminta kelompok untuk dapat menindaklanjuti proses rekrutmen komunitas di tahun berikutnya. Walaupun dari segi intervensi tergolong berhasil, namun terdapat beberapa kendala dialami oleh kelompok seperti intervensi yang hanya dapat dilakukan satu kali karena mengikuti jadwal dari pengurus komunitas.